1995
DOI: 10.1128/mcb.15.2.1060
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p53-Mediated Transcriptional Repression and Apoptosis by the Adenovirus E1B 19K Protein

Abstract: BRK cell lines that stably express adenovirus E1A and a murine temperature-sensitive p53 undergo apoptosis when p53 assumes the wild-type conformation. Expression of the E1B 19,000-molecular-weight (19K) protein rescues cells from this p53-mediated apoptosis and diverts cells to a growth-arrested state. As p53 likely functions as a tumor suppressor by regulating transcription, the ability of the E1B 19K protein to regulate p53-mediated transactivation and transcriptional repression was investigated. In promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
175
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 56 publications
10
175
1
2
Order By: Relevance
“…Furthermore, studies have also shown that antiapoptotic proteins such as Bcl-2 and adenovirus E1B 19-kD protein can inhibit p53-mediated apoptosis. Interestingly, these two proteins can also inhibit p53-mediated transrepression but not transactivation (Sabbatini et al, 1995a;Shen and Shenk, 1994). These results would be consistent with the transrepression function of p53 being associated with its apoptotic function.…”
Section: Uncoupling Of the Apoptotic Function Of P53 From Its Transacsupporting
confidence: 73%
“…Furthermore, studies have also shown that antiapoptotic proteins such as Bcl-2 and adenovirus E1B 19-kD protein can inhibit p53-mediated apoptosis. Interestingly, these two proteins can also inhibit p53-mediated transrepression but not transactivation (Sabbatini et al, 1995a;Shen and Shenk, 1994). These results would be consistent with the transrepression function of p53 being associated with its apoptotic function.…”
Section: Uncoupling Of the Apoptotic Function Of P53 From Its Transacsupporting
confidence: 73%
“…Among these genes, the viral genes E1B19kD and E1B55kD, cellular gene bcl2 and oncogenic cHa-ras that are complementing with E1A to fully transform cells of di erent origin. E1A+E1B19kD transformants expressing the wild type p53 reveal a p53-dependent block at G1/S boundary of the cell cycle (Sabbatini et al, 1995). In contrast, E1A+cHa-ras-transformed cells are unable to be arrested at G1/S by over-expression of wild type p53 (Lin et al, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…High e ciency of foci formation in the presence of Ad5-E1A can be achieved when E1A cooperates with genes that suppress the programmed cell death allowing the E1A expression at high levels (Lin et al, 1995;Sabbatini et al, 1995). Among these genes, the viral genes E1B19kD and E1B55kD, cellular gene bcl2 and oncogenic cHa-ras that are complementing with E1A to fully transform cells of di erent origin.…”
Section: Introductionmentioning
confidence: 99%
“…However, at 328C the permissive temperature, p53 is wild-type and cells undergo apoptosis. Expression of the E1B 19K protein in the E1A plus p53(Val135) transformed BRK cell line can overcome apoptosis induced by wild-type p53 at 328C (Debbas and White, 1993) although, the ability of p53 to induce growth arrest is not a fected by the expression of E1B 19K (Sabbatini et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%